Preliminary assesment of variability of Suspended load changes in cross-section Chalupki on Odra River - Robert Głowski; Robert Kasperek (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The aim of the study was to analyse the reasons for the occurrence of intensive suspended load transport in the area of meander 1. The river load transport caused significant morphological changes in the Upper Oder River bed system.